FRI0461 Do the anti-saccharomyces cerevisiae antibodies (ASCA) modify the ankylosing spondylitis phenotype?. (23rd January 2014) - Maillet, J.; Ottaviani, S.; Nicaise-Roland, P.; Gill, G.; Palazzo, E.; De Chaisemartin, L.; Meyer, O.; Chollet-Martin, S.; Dieudé, P.
Abstract : Background: The anti-saccharomyces cerevisiae antibodies (ASCA) are serum markers in inflammatory bowel disease (IBD) either Crohn's disease (CD) or ulcerative colitis (UC), which are present in almost 50% patients with CD. In spondylarthritis (SpA), there is a lack of specific markers to help the clinician for the diagnosis and management of the disease. ASCA, often the IgA form, are found in 30% patients who have SpA even without any digestives symptoms. Objectives: We performed in our department a cross-sectional study evaluating the prevalence and the influence of the ASCA status on disease phenotype. Methods: 223 SpA patients (all fulfilling the ESSG criteria) were included. Demographic (age, gender, disease duration), clinical (axial and/or peripheral presentation, presence of arthritis, enthesitis, spine pain, psoriasis, uveitis, IBD), biological ( HLAB27 status) data, and use of treatments (DMARDs, anti-inflammatory drugs and anti-TNFa) were collected. For each patient, ASCA determination was performed by serum indirect immunofluorescence. Demographic characteristics, clinical features and blood tests of SpA patients ASCA positive and negative were compared. Results: 223 SpA patients (mean age: 46.7±14.4 years, 54.3% men, 55% HLAB27+) were included. The mean disease duration was 105.7±116.9 months. 86% of patients had axial involvement, 70.4% had peripheral involvement. 10.6% suffered of IBD. 20.6%, 22.9% and 61.2% of patients received anti-inflammatory drugs, DMARDs or anti-TNFa respectively. Among the 223 SpA patients included, positivity of ASCA was observed in 24.7% (n= 55) (IgG: 9.4%; IgA: 21.1%). The positivity of ASCA was associated with lower frequency of HLAB27 positivity (60.4% vs 38.3%, P = 0.011) and axial involvement (91.1% vs 69.9%, P < 0.0001). Moreover, ASCA positivity was more frequently observed in patients with isolated peripheral involvement (10.7% vs 30.9%, P = 0.001), arthritis (27.3% vs 59.3%, P < 0.0001) and dactylitis (9.8% vs 26.9%, P = 0.004). There was no difference between ASCA+ and ASCA- SpA patients regarding the presence of uveitis, IBD, enthesitis and psoriasis. Conclusions: These findings suggest that ASCA could influence the phenotype of SpA, the ASCA positive status being associated with peripheral involvement, including dactylitis, and a decrease of frequency of HLA B27 antigen. Disclosure of Interest: None Declared